Ticks without borders: microbiome of immature neotropical tick species parasitizing migratory songbirds along northern Gulf of Mexico - Karim, Shahid; Zenzal, Theodore J.; Beati, Lorenza; Sen, Raima; Adegoke, Abdulsalam; Kumar, Deepak; Downs, Latoyia P.; Keko, Mario; Nussbaum, Ashly; Becker, Daniel J.; Moore, Frank R. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionThe long-distance, seasonal migrations of birds make them an effective ecological bridge for the movement of ticks. The introduction of exotic tick species to new geographical regions can cause the emergence of novel tick-borne pathogens. This study examined the prevalence of exotic tick species parasitizing migratory songbirds at stopover sites along the northern Gulf of Mexico using the mitochondrial 12S rRNA gene.MethodsOverall, 421 individual ticks in the genera Amblyomma, Haemaphysalis, and Ixodes were recorded from 28 songbird species, of which Amblyomma and Amblyomma longirostre were the most abundant tick genera and species, respectively. A high throughput 16S ribosomal RNA sequencing approach characterized the microbial communities and identified pathogenic microbes in all tick samples.Results and discussionMicrobial profiles showed that Proteobacteria was the most abundant phylum. The most abundant pathogens were Rickettsia and endosymbiont Francisella, Candidatus Midichloria, and Spiroplasma. Permutation multivariate analysis of variance revealed that the relative abundance of Francisella and Rickettsia drives microbial patterns across the tick genera. We also noted a higher percentage of positive correlations in microbe-microbe interactions among members of the microbial communities. Network analysis suggested a negative correlation between a) Francisella and Rickettsia and, b) Francisella and Cutibacterium. Lastly, mapping the distributions of bird species parasitized during spring migrations highlighted geographic hotspots where migratory songbirds could disperse ticks and their pathogens at stopover sites or upon arrival to their breeding grounds, the latter showing mean dispersal distances from 421–5003 kilometers. These findings spotlight the potential role of migratory birds in the epidemiology of tick-borne pathogens.